Investigating Indonesian Textbooks Readability Using Fry Graph Formula - Sarimanah, Eri; Soeharto, Soeharto; Ramadhanti, Anissa; Suhendra, Suhendra; Efendi, Roy (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
Learning the Indonesian language cannot be separated from the use of textbooks. In using textbooks, teachers must consider several aspects, especially text readability. This study aims to measure text readability in Indonesian textbooks using the Fry Graph Formula and determine the suitability of the text used in the book with the student's school level. The present study applied the descriptive analysis and quantitative approach method to count and analyze texts in several Indonesian language textbooks readability using the Fry graph formula. Three Indonesian language textbooks with 45 measured text in 11th grade were analyzed. This study found that 25 texts showed the results "Not Appropriate", 16 texts showed the results "Appropriate", and four texts showed the results "Invalid". Based on the analysis, the number of readabilities of text in Indonesian language textbooks was easy for textbooks at 11th grade. The findings in this study can help the teacher adjust and choose the suitable teaching materials in Indonesian language textbook to improve teaching and learning quality. Before selecting a leading textbook as a learning source, we suggest teachers analyze text readability to improve learning efficiency and quality.